The crisis of global capitalism : [open society endangered] - Soros, George (Great Britain : Little Brown and Company, 1998)
Soros dissects the current crisis and economic theory in general, revealing how theoretical assumptions have combined with human behavior to lead to today's mess. He shows how unquestioning faith in market forces blinds kus to cruc instablilities have chain-reacted to cause the current crisis - a crisis that has the potential to get much, much worse.
Includes bibliographical references.
Koleksi sumbangan Prof. Dr. Mohd. Safar Hasim.
Koleksi Sumbangan: Dr. Mohamad Nasrin Mohamad Nasir.
Keywords: Financial crises; Capitalism; International finance; Economic history -- 1990-